Let a and b be positive real numbers satisfying the following condition:
a 3 + b 3 = a − b
Also k = a 2 + 4 b 2
Find the correct option:
Hint : AM-GM Inequality
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution @Tom Engelsman . But can u try it out using AM GM inequality??
Log in to reply
You sure can, Mayank, but personally I'm not a big fan of AM-GM. My mind works best in the realm of functions (such as my k = f(N) solution above). Depending on the problem, AM-GM sometimes requires WAY more work than is needed due to additional tricks and conversions of variables to make them adhere to the basic inequality format. My two-cents :) Good problem by the way.
Here's another method to solve the question:
Given :
x 3 + y 3 = x − y
x − y x 3 + y 3 = 1
x − y x 3 − y 3 + 2 y 3 = 1
x − y x 3 − y 3 + x − y 2 y 3 = 1
Using the identity : x 3 − y 3 = ( x − y ) ( x 2 + x y + y 2 )
We get the following:
x 2 + x y + y 2 + x − y 2 y 3 = 1
x 2 + 2 y 2 − y 2 + x y + x − y 2 y 3 = 1
x 2 + 2 y 2 + [ y ( x − y ) + x − y 2 y 3 ] = 1
Now , applying AM GM inequality on the terms inside the bracket we get :
1 ≥ x 2 + 2 y 2 + 2 2 y ² > x 2 + 2 y 2 + 2 y 2
So x 2 + 4 y 2 < 1
Hence k < 1
Also try my problem "What an Exam"
Problem Loading...
Note Loading...
Set Loading...
Let b = N ⋅ a ( N ∈ R + ) so that a , b ∈ R + . Substituting this value into the above equation produces:
a 3 + ( N a ) 3 = a − N a ⇒ ( 1 + N 3 ) a 3 = ( 1 − N ) a ⇒ a 2 = 1 + N 3 1 − N .
If k = a 2 + 4 b 2 , then we have k = a 2 + 4 N 2 a 2 = ( 1 + 4 N 2 ) ( 1 + N 3 1 − N ) . Since k is the sum of the squares of two positive reals, we obviously have k = 1 + N 3 ( 1 + 4 N 2 ) ( 1 − N ) > 0 . This inequality is only satisfied for 0 < N < 1 . Upon plotting k as a function of N we find that it has a vertical asymptote at N = − 1 and a horizontal asymptote at k = − 4 and satisfies the following range intervals:
k ∈ ( − ∞ , − 4 ) over N ∈ ( − ∞ , − 1 ) ;
k ∈ [ 1 , ∞ ) over N ∈ ( − 1 , 0 ] ;
k ∈ ( 0 , 1 ) over N ∈ ( 0 , 1 ) ;
k ∈ ( − 4 , 0 ] over N ∈ [ 1 , ∞ ) .
If we require N ∈ ( 0 , 1 ) , then k < 1 is the correct choice.